ANALYSIS OF ELSA’S CHARACTER DEVELOPMENT IN THE FROZEN I ANIMATION AS POTENTIAL MODEL FOR CHARACTER EDUCATION - Olivia Sutra Ningrum (Faculty of Education, 2025)
This research analyzes Elsa’s character development in Frozen I and evaluates its potential as a model for character education, emphasizing the importance of creative and appropriate media in teaching values. With growing concerns over youth character decline due to unfiltered digital content, character education becomes essential for shaping intelligent and moral individuals. Animated films like Frozen offer engaging, relatable narratives that can effectively convey moral lessons, making them valuable tools for educational purposes. This study applies Ki Hajar Dewantara’s philosophy and Indonesia’s Emancipated Curriculum, viewing character education as holistic. It also considers research showing animation can convey moral values effectively with adult guidance. Using Fairclough’s critical discourse analysis, Elsa’s scenes are categorized into Introduction, Confrontation, and Resolution, then analyzed to assess their value for character education.
februari 2026 Rudi H
Keywords: ELSA’S CHARACTER; DEVELOPMENT; FROZEN I ANIMATION